2010
DOI: 10.1128/iai.00245-09
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid DiminishesStaphylococcus aureusCapsular Polysaccharide Type 5 Expression

Abstract: Capsular polysaccharides (CP) of serotypes 5 (CP5) and 8 (CP8) are major Staphylococcus aureus virulence factors. Previous studies have shown that salicylic acid (SAL), the main aspirin metabolite, affects the expression of certain bacterial virulence factors. In the present study, we found that S. aureus strain Reynolds (CP5) cultured with SAL was internalized by MAC-T cells in larger numbers than strain Reynolds organisms not exposed to SAL. Furthermore, the internalization of the isogenic nonencapsulated Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 61 publications
5
26
0
Order By: Relevance
“…As shown in Figure 6A, SAL treatment of planktonic cultures of the Newman strain caused a perturbation of the surface polysaccharide composition that was not reverted by iron addition. In the light of our previous work and the results described herein it is suggested that CP instead of PIA expression is affected by SAL treatment due to the fact that CP production under planktonic culture conditions is limited (Alvarez et al, 2010). In contrast to planktonic growth, PCA of the Newman biofilms revealed that iron limitation by SAL exposure induced polysaccharide production alterations that were partially reverted by iron addition (Figure 6B).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…As shown in Figure 6A, SAL treatment of planktonic cultures of the Newman strain caused a perturbation of the surface polysaccharide composition that was not reverted by iron addition. In the light of our previous work and the results described herein it is suggested that CP instead of PIA expression is affected by SAL treatment due to the fact that CP production under planktonic culture conditions is limited (Alvarez et al, 2010). In contrast to planktonic growth, PCA of the Newman biofilms revealed that iron limitation by SAL exposure induced polysaccharide production alterations that were partially reverted by iron addition (Figure 6B).…”
Section: Resultssupporting
confidence: 50%
“…The expression of virulence factors and regulatory genes is modified by SAL in several bacterial species (Pomposiello et al, 2001; Denkin et al, 2005). Previous findings from our laboratory demonstrated that exposure of encapsulated S. aureus strains to low concentrations of SAL reduced CP production and increased the Eap adhesin expression under planktonic conditions (Alvarez et al, 2010, 2011). On the other hand, Johnson et al (2008) observed that an increase of Eap expression under depleted iron conditions contributed to biofilm formation, a finding that becomes relevant due to the fact that SAL can form complexes with iron cations (Cheng et al, 1996; Pozdnyakov et al, 2015).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Preimmune rabbit serum and absorbed sera were nonreactive by immunodiffusion against bacterial extracts containing CP5 and CP8. Isolates that were nonreactive in the colony immunoblot assay were confirmed to be NT by the double immunodiffusion assay, using the capsule extracts as previously described (35). Briefly, a 1% agarose gel was prepared on a glass slide and wells were punched in a circular fashion around a central hole.…”
Section: Methodsmentioning
confidence: 99%